Research on expert opinion analysis on the influence of motivation factors on swimming and performance at the age of 9-10 years - Petre Dan Ionuț; Nedelcu Răzvan Ioan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
The review of the findings of some studies carried out in the last 5-10 years has brought to attention various information about the training process and the physical preparation of children. Previous similar approaches have often been briefing in relation to children's motivation for swimming, at least from the point of view of character. If there were some effects of motivation, they are either irrelevant or you didn't target 9-10-year-old. Taking into account these aspects and based on the analysis of specialized literature, the present research started from the premise of promoting effective methods and techniques to stimulate the motivation of children aged 9-10 years to practice swimming.